Proposing a Liquidity Risk Management Model in Iraqi Banks - Jabbar Mahammad, Ahamad; Madanchi Zaj, Mahdi; Zomorodian, Gholamreza; Kordlouie, Hamidreza (Business, Marketing, and Finance Open, 2025)
The present study was conducted with the aim of proposing a liquidity risk management model for banks in Iraq. Methodologically, this research is theoretical-applied in terms of purpose, based on a survey research design and follows a descriptive–inductive reasoning method. Due to the nature of the data and the analytical approach, the study adopts a mixed-methods (quantitative–judgmental) framework. Initially, based on a knowledge domain analysis and a qualitative content analysis model, liquidity management indicators and their influencing factors were identified. Subsequently, through a persuasive Delphi survey, 20 experts and academic professionals specializing in the banking sector of Iraq were selected using a non-random method. Using the fuzzy network multi-criteria decision-making model, the most influential measurement indicators for the variables were evaluated and refined, and the final proposed model was developed. After conducting diagnostic tests—including the assessment of normal distribution of variables, homogeneity of variances, confirmatory factor analysis, and validation of the structural equation modeling (SEM) framework—advanced SEM models, path analysis, and regression estimation techniques were employed to interpret the direct relationship between liquidity management and its influencing factors, as well as the impact of moderating variables on these relationships. Finally, the coefficient of determination was used to validate the estimated relationships, and the Student's t-test was employed to measure the significance level of these relationships. The synthesized results indicated that organizational cognition, adaptability and alignment, competitive pressure, complexity, government support, managerial capabilities, market uncertainty, comparative advantage, technical capabilities, and stakeholder engagement all have a positive and significant impact on liquidity management in Iraqi banks.